2021
DOI: 10.1111/ele.13945
|View full text |Cite
|
Sign up to set email alerts
|

Climate change impacts plant carbon balance, increasing mean future carbon use efficiency but decreasing total forest extent at dry range edges

Abstract: Carbon use efficiency (CUE) represents how efficient a plant is at translating carbon gains through gross primary productivity (GPP) into net primary productivity (NPP) after respiratory costs (R a ). CUE varies across space with climate and species composition, but how CUE will respond to climate change is largely unknown due to uncertainty in R a at novel high temperatures. We use a plant physiological model validated against global CUE observations and LIDAR vegetation canopy height data and find that model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 70 publications
1
19
0
Order By: Relevance
“…However a warming- induced increased respiration cost might curb these trends and even offset a positive GPP and/or NPP response to increasing atmospheric CO 2 concentration, as indicated by some other modeling and experimental studies (Way et al, 2008; Gustavson et al, 2017; Collalti et al, 2018; but see Reich et al, 2016). For example, Mathias and Trugman (2021) showed a potential future unsustainable growth for boreal and temperate broadleaved forests, with the net overall effect of decreased NPP. Other studies already indicated that combined impacts of warming and increasing atmospheric CO 2 concentration might cause forests to grow faster and mature earlier but also to die younger (Kirschbaum, 2005; Collalti et al, 2018, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However a warming- induced increased respiration cost might curb these trends and even offset a positive GPP and/or NPP response to increasing atmospheric CO 2 concentration, as indicated by some other modeling and experimental studies (Way et al, 2008; Gustavson et al, 2017; Collalti et al, 2018; but see Reich et al, 2016). For example, Mathias and Trugman (2021) showed a potential future unsustainable growth for boreal and temperate broadleaved forests, with the net overall effect of decreased NPP. Other studies already indicated that combined impacts of warming and increasing atmospheric CO 2 concentration might cause forests to grow faster and mature earlier but also to die younger (Kirschbaum, 2005; Collalti et al, 2018, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We used the HOTTER model (the Hydraulic Optimization Theory for Tree and Ecosystem Resilience model; Mathias & Trugman, 2022; Trugman, Anderegg, Wolfe, et al, 2019; Figure S1), a physiologically based tree model with a realistic representation of gas exchange (Eller et al, 2018) and a detailed representation of plant hydraulics (Trugman et al, 2018) to quantify spatial variations in tree water status, hydraulic stress, and carbon gain across gradients in climate and plant traits in the continental United States. Our model experiments combined hydraulic trait maps based on high‐resolution species distribution and abundance data derived from the US Forest Service Forest Inventory and Analysis Program with a large hydraulic trait database (Trugman et al, 2020), tree height measured remotely by satellite, and daily historical and future climate forcing data (see Section 2).…”
Section: Methodsmentioning
confidence: 99%
“…HOTTER combines key physiological processes of photosynthesis, autotrophic respiration, and plant hydraulics to simulate plant water status, carbon gain, and hydraulic stress. Here, we updated previous versions of the model (Mathias & Trugman, 2022; Trugman et al, 2018), to include a new stomatal optimization, the Stomatal Optimization Based on Xylem Hydraulics (SOX) (Eller et al, 2018). In this new version, stomatal behavior is governed by a leaf scale trade‐off between the carbon gain of assimilation and a cost function based on the percent loss of conductivity in the tree xylem.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However a warming-induced increased respiration cost might curb these trends and even offset a positive GPP and/or NPP response to increasing atmospheric CO 2 concentration, as indicated by some other modeling and experimental studies (Way et al, 2008;Gustavson et al, 2017;Collalti et al, 2018;but see Reich et al, 2016). For example, Mathias and Trugman (2021) showed a potential future unsustainable growth for boreal and temperate broadleaved forests, with the net overall effect of decreased NPP. Other studies already indicated that combined impacts of warming and increasing atmospheric CO 2 concentration might cause forests to grow faster and mature earlier but also to die younger (Kirschbaum, 2005;Collalti et al, 2018.…”
Section: Limited Leeway To Increase Carbon Uptake and Woody Stocks Wi...mentioning
confidence: 99%